Respiratory health in chrysotile asbestos miners in British Columbia: a longitudinal study. Issue 7 (July 1988) - Enarson, D A; Embree, V; MacLean, L; Grzybowski, S
Abstract : A respiratory survey was undertaken in chrysotile asbestos miners in British Columbia consisting of a questionnaire, spirometry, chest radiography, and physical examination. The tests were performed in 1977 and again in 1983. The population groups studied included 63 "exposed" (working in the plant more than nine years), 52 "controls" (working in the plant less than five years), and 38 residents of the village at the minesite. A subset of 39 was identified with high exposure (worked in the mill more than five years). Measured levels of environmental particulates were similar over the entire period of operation of the plant (1.4 to 14.0 million particles per cubic foot and 0.7-88.0 fibres/cc in the mill; 0.2 to 2.7 mpcf and 0.6 to 9.3 f/cc in the mine). The exposed groups were more likely to report cough and breathlessness than the two other groups and were also more likely to have abnormal FVC and chest x ray films (the latter not significant, p greater than 0.05) and to be more likely to have a combination of these abnormalities. There was no trend to progression in the combination of abnormalities associated with exposure on follow up. The heavily exposed group showed a significantly worse trend in FVC. This adverse trend was confined to those with initial abnormalities. Tobacco smoking did not increase the trend to progression in this group.